Perancangan Aplikasi Forcoms Menggunakan Metode User Centered Design - Abhirama Adnyana, I Gusti Agung Gde; Mahendra, S.Kom., M.Kom., Ida Bagus Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Building application are the hardest thing, specially the user interface. User Interface be the first thing user see and the pointer between application and user it’s self. User Center Design are design by valuing from user base, not like other method for designing. UCD create design from feedback user and making the valuable design for user to use and the design methodology for understandable design. in this case using UCD and implement the design to android application using programming language like java.